2015
DOI: 10.1080/00222933.2015.1006281
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of threeAristolochia-feeding Papilionids(Archon apollinus, Zerynthia polyxenaandZerynthia cerisy)in Greek Thrace

Abstract: Comparative studies of co-occurring species using overlapping resources may help in understanding the mechanisms supporting biotic diversity in species-rich regions, such as the Mediterranean region of Europe. Three Papilionidae butterflies, Archon apollinus, Zerynthia cerisy and Zerynthia polyxena, develop on Aristolochia plants and co-occur in Greek Thrace. We used mark-recapture to describe adult demography and dispersal, and searched for eggs and larvae to assess host plants and microhabitat preferences. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The preference of more irradiated patches of plants could be explained by a faster development of immatures with warmer temperatures, as seen in other Papilionidae species, namely the larvae of Papilio glaucus (Scriber and Lederhouse 1983) and the pupae of Parnassius mnemosyne (Valimaki and Itamies 2005). In these species, and in Z. polyxena and Z. cerysi as well, a higher concentration of larvae occurs in sunlight areas (Slancarova et al 2015).…”
Section: Implication For Conservation In Situmentioning
confidence: 89%
“…The preference of more irradiated patches of plants could be explained by a faster development of immatures with warmer temperatures, as seen in other Papilionidae species, namely the larvae of Papilio glaucus (Scriber and Lederhouse 1983) and the pupae of Parnassius mnemosyne (Valimaki and Itamies 2005). In these species, and in Z. polyxena and Z. cerysi as well, a higher concentration of larvae occurs in sunlight areas (Slancarova et al 2015).…”
Section: Implication For Conservation In Situmentioning
confidence: 89%
“…Zerynthia polyxena adults inhabit a wide range of biotopes in Europe (van Sway et al, 2006), including meadows (Vovlas et al, 2014), black locust plantations, and hummocks (Batáry et al, 2008; Örvössy et al, 2014), as well as open woodland and close forest (Slancarova et al, 2015). Conversely to what Hayes et al (2018) found for H. lucina , we found that adults preferred gentler slopes facing southwest or south (see also Weiss et al, 1988) with a modest presence of forest area.…”
Section: Discussionmentioning
confidence: 99%
“…The State of Nature in the EU (2019)—Article 17 reporting). In Europe, Z. polyxena larvae are oligophagous, feeding on Aristolochia species; often, they are locally monophagous (Piccini et al, 2021; Slancarova et al, 2015; Vovlas et al, 2014). Indeed, Z. polyxena has specialist host plant requirements that are known to make species sensitive to habitat changes (Öckinger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Zerynthia cassandra is a sedentary species, with a very limited flying range (up to a few hundred metres; Celik, 2012; Vovlas et al ., 2014), despite longer dispersal events within the range of a few kilometres are possible (e.g. as observed in Z. polyxena in Greece; Slancarova et al ., 2015).…”
Section: Methodsmentioning
confidence: 99%